Analisis Struktur Modal Kaitannya dengan Manfaat Ekonomi Langsung Pada Koperasi X (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
In practice, cooperatives are institutions that are not only profit or profit oriented profit oriented but also on service or service oriented. One cooperative that is oriented towards these two aspects is Cooperative X, where this cooperative is a cooperative multipurpose which in carrying out its business activities has several business units to support or serve the needs of its members. With the existence of several business units to support members' needs, of course Cooperative X needs to serve its members well. One of them is by providing price benefits, both selling prices and purchasing prices, to members of the cooperative. Where the intended benefits are better known as direct economic benefits. The rise and fall of economic benefits is directly related to the management of the cooperative's capital structure which will later finance the cooperative's business activities. The aim of this research is to obtain an overview of the relationship between capital structure and direct economic benefits. The method used in this research is a case study and analyzed using descriptive analysis. The results of this research show that there is a negative relationship between capital structure and direct economic benefits, which means that when the capital structure of a cooperative decreases, direct economic benefits will increase. This can be seen from the development of the capital structure and direct economic benefits in 2022. Based on this, it can be concluded that in carrying out its business activities, Cooperative X has managed or used its loan capital well.